(untitled) (Journal of the College of Basic Education, 2025)
The research aims to identify: Measure selfish bias among gifted school students. Identify selfish bias among gifted school students. To verify this, the researcher conducted the following procedures: Constructing and applying a scale of egocentric bias among gifted school students. The researcher used the descriptive approach, as he constructed a scale of egocentric bias according to expectancy theory (Kahneman & Schater, 2011) to define the concept of egocentric bias. The scale consisted of 30 items in its final form. After that, it was applied to the statistical analysis sample consisting of (400) students, and the psychometric statistical properties of the scale were extracted from the validity and reliability, as the correlation coefficient for the reliability of the scale by the retest method reached (0.80). The Cronbach’s correlation coefficient was 0.84. To achieve the research objective, the researcher used a single-sample t-test, and the results showed that there is a selfish bias among students of gifted schools at a high level. Based on the results, the researcher came up with a number of conclusions, recommendations, and proposals